Training and Assistance in the Preparation of Promotional Media for Junior High Schools and MTs Muhammadiyah Malang City - Eggy Fajar Andalas; Hari Windu Asrini (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
The large number of junior high schools, zoning system, and pandemic raises problems regarding the decline in the number of junior high school students and MTs Muhammadiyah in Malang City. There are quite a lot of factors behind the number of registrants. However, as an effort to solve the problem, the preparation of promotional media with the right language and media is expected to help increase the number of registrants. This service activity aims to provide training and assistance in the preparation of school promotion media for Muhammadiyah Junior High Schools and MTs in Malang City. Devotion is carried out by the method of 4 stages of the creative process, namely preparation, incubation, illumination, and verification. Based on the activities that have been carried out, it was found that one of the problems in promoting the registration of new students was the lack of ability of teachers to determine the superior activities that would be offered to prospective students. In addition, the visual communication design in the poster has also not been able to provide clear information to the reader. Through intensive training and mentoring, satisfactory results are obtained. Teachers can create interesting and targeted school promotional media.